Study on the morphology and agroecology of creat (Andrographis panculata ness.) in various habitat - BAMBANG PUJIASMANTO; JODY MOENANDIR; SYAMSULBAHRI SYAMSULBAHRI; KUSWANTO KUSWANTO (Society for Indonesian Biodiversity, 2007)
Raw material supply which still depends on nature has caused genetic erotion of medicinal plants. The objectives of the research were to study creat (Andrographis paniculata Ness.) morphology; and agroecology in many habitat for cultivated be medical substance. The research were conducted at three different locations, ie. at lowland (< 400 m above sea level), middleland (400 – 700 m asl.), and upland (> 700 m asl.). The result showed that creat growth on 180 m – 861 m above sea level with environmental conditions : temperature 20.320C – 26.930C, relative humidity 78% - 87%, perticipation 2053.2 mm/ year – 3555.6 mm/ year. The creat can growth on soil mineral that contains N medium, P low, K medium, Mg low, Ca verylow until low ,C organic low until medium, and pH less acid until acid. The heihgt plant of creat in middleland is the highest of in lowland and upland, that also leaf of creat. The flower, fruit, and root of creat as good as in the habitat various. The highest andrographolid contain in middleland (2.27%), whereas in lowland (1.37%) and upland (0.89%).© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: agroecology, creat morphology